LEADERSHIP IN SWEDISH NURSING HOMES IN RELATION TO PERSON-CENTRED CARE AND STAFF WORK SITUATION. (11th November 2018) - Backman, A; Sjögren, K; Lövheim, H; Edvardsson, D
Abstract: Little is known about leading the provision of person-centred care and the creation of a healthy work environment. The aim was to explore leadership in relation to person-centred care and the work situation of staff in Swedish nursing homes. A cross-sectional nation-wide design was employed, including staff (n=3605) in 169 nursing homes in Sweden. Surveys about leadership, person-centred care, job strain and social support were used. Data were explored by descriptive statistics, simple and multiple regression analyses. Also, data from 11 semi-structured interviews with 12 nursing home managers were analyzed by Qualitative content analysis. The findings showed that leadership was characterized by; experimenting with new ideas; controlling work closely, relying on his/her subordinates, coaching and giving direct feedback followed by handling conflicts constructively. Further, leadership was beneficially associated with person-centred care, psychosocial climate, job strain and social support. Also, leading person-centred care could be outlined as four leadership processes.